A Viable Residential DC Microgrid for Low Income Communities – Architecture, Protection and Education - (:unkn) unknown (My University, 2019)
The availability of fossil fuels in the future and the environmental effects such as the carbon footprint of the existing methodologies to produce electricity is an increasing area of concern. In rural areas of under-developed parts of the world, the problem is lack of access to electrification. DC microgrids have become a proven solution to electrification in these areas with demonstrated exceptional quality of power, high reliability, efficiency, and simplified integration between renewable energy sources (principally solar PV) and energy storage. In the United States, a different problem occurs that can be addressed with the same DC microgrid approach that is finding success internationally. In disinvested, underserved communities with high unemployment and low wages, households contribute a significant portion of their income towards the fixed cost of their electrical utility connection, which by law must be supplied to every household. In order to realize such a microgrid in these communities, there are three major areas which need to be accounted for. Firstly, there needs to be a custom architecture for the community under consideration and it needs to be economical to match the needs of the underserved community. Secondly, DC microgrid for home energy interconnection is potentially less complex and less expensive to deploy, operate and maintain however, faster protection is a key element to ensuring resilience, viability and adoptability. Lastly, these types of efforts will be sustainable only if the people in the community are educated and invested in the same as they are the key stakeholders in these systems. This dissertation presents an approach to make the DC Microgrid economically feasible for low income households by reducing the cost they incur on electric bills. The approach is to overlay a DC system into homes that have a utility feed in order to incorporate renewable energy usage into an urban setting for the express purpose of driving down individual household utility costs. The results show that the incorporation of a certain level of “smart” appliances and fixtures into the renovation of vacated homes and the use of a microgrid to enable sharing of renewable energy, such as solar power combined with energy storage, between homes in the proposed architecture yields the least expensive option for the patrons. The development of solid state circuit breakers that interface between the microgrid and the home DC power panels helps in faster protection of the DC system. In this dissertation, a SiC JFET based device is designed and built to protect against DC faults at a faster rate than the available solutions. The prototype is tested for verification and used to discriminate against short circuit faults and the results show the successful fault discrimination capabilities of the device. A basic system level simulation with the protection device is implemented using Real Time Hardware in the loop platform. Finally, as a part of engaging the community members, the high school kids in the area who might potentially be living in some of the houses in this community are being educated about the microgrid, appliances and other technologies to get a better understanding of STEM and hopefully inspiring them to pursue a career in STEM in the future.
Keywords: Architecture; Community; DC Microgrid; JFET; Protection; STEM